Correlation between changes in Timed Up and Go performance and cognition in older people with mild cognitive impairment: A longitudinal study. (April 2022) - Melo, Laura M.; Ansai, Juliana H.; Ferreira, Ana C.V.G.; Silva, Danielle C.P.; Vale, Francisco A.C.; Takahashi, Anielle C.M.; Andrade, Larissa P.
Abstract: Background: Compare changes in performance on subtasks of the Timed Up and Go test over 32 months in older adults with and without mild cognitive impairment; analyze the correlation between frontal cognitive functions at baseline and changes in Timed Up and Go subtasks over time. Methods: A longitudinal study was conducted involving 31 older adults (15 with and 16 without cognitive impairment). Functional mobility was assessed at both evaluations using an adapted version of the Timed Up and Go test and the Qualisys motion system. The test was divided into five subtasks: sit-to-stand, walking forward, turn-to-walk, walking back and turn-to-sit. Cognition was assessed at baseline using the Frontal Assessment Battery and the Clock Drawing Test. Findings: Significant differences in changes in the sit-to-stand subtask over time were found between groups. The difference in the time required to conclude this subtask was greater in the older adults with cognitive impairment. However, the difference in kinematic variables (peak trunk speed and range of motion) was greater in the group without cognitive impairment. Strong and moderate correlations were found between frontal cognitive functions and changes in Timed Up and Go subtasks, especially those involving transitions (sit-to-stand, turn-to-walk and turn-to-sit) in both groups. Interpretation: Motor intervention protocols should incorporate the sit-to-stand subtask in older adults with mild cognitive impairment. Moreover, changes in more complex subtasks seem to be related to frontal cognitive performance at baseline. Therefore, treatments that combine motor and cognitive functions should be administered to older adults regardless of cognitive impairment. Highlights: Cognitively impaired adults spent less time during the sit-to-stand subtask. Cognition has a role in postural control among cognitively impaired adults. Changes in more complex subtasks are related to the initial cognitive performance.